2014
DOI: 10.1164/rccm.201404-0716cp
|View full text |Cite
|
Sign up to set email alerts
|

Gleaning Knowledge from Data in the Intensive Care Unit

Abstract: It is often difficult to accurately predict when, why, and which patients develop shock, because signs of shock often occur late, once organ injury is already present. Three levels of aggregation of information can be used to aid the bedside clinician in this task: analysis of derived parameters of existing measured physiologic variables using simple bedside calculations (functional hemodynamic monitoring); prior physiologic data of similar subjects during periods of stability and disease to define quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 23 publications
(10 reference statements)
0
24
0
Order By: Relevance
“…However, previous comparison studies have suggested that machine learning methods can be more accurate than traditional logistic regression across a wide variety of subject areas (6). Thus, when the stakes are high, it is important to consider techniques beyond standard regression to optimize accuracy (7). …”
Section: Introductionmentioning
confidence: 99%
“…However, previous comparison studies have suggested that machine learning methods can be more accurate than traditional logistic regression across a wide variety of subject areas (6). Thus, when the stakes are high, it is important to consider techniques beyond standard regression to optimize accuracy (7). …”
Section: Introductionmentioning
confidence: 99%
“…23 This and other analytic approaches to aid clinical decisions can be incorporated into intelligent and integrated monitoring systems. 24, 25 In addition, they may help the bedside caregiver to decide to call for help in a more objective and “defensible” manner, since there are human factors which also serve as barriers to recognizing instability and increased failure-to-rescue. 26 In one study of 118 ward nurses, 30% reported hesitancy to call a MET.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the data are mainly collected for patient routine care or for a specific purpose such as a trial and are not used “outside.” This is progressively changing and big data is currently being implemented at patients’ bedside and in clinical research. For example, “fused parametric measures” are routinely used to determine the level of severity [49]. In clinical trials, “pooled trial data” seems to be an inevitable evolution that might be very useful in the future.…”
Section: Main Textmentioning
confidence: 99%